Sustained reduction in bronchial hyperresponsiveness with inhaled fluticasone propionate within three days in mild asthma: time course after onset and cessation of treatment. Issue 6 (1st June 2003) - Sovijärvi, A R A; Haahtela, T; Ekroos, H J; Lindqvist, A; Saarinen, A; Poussa, T; Laitinen, L A
Abstract : Background: Bronchial hyperresponsiveness (BHR) is characteristic of asthmatic airways, is induced by airway inflammation, and is reduced by inhaled corticosteroids (ICS). The time course for the onset and cessation of the effect of ICS on BHR is unclear. The effect of inhaled fluticasone propionate (FP) on BHR in patients with mild persistent asthma was assessed using time intervals of hours, days and weeks. Methods: Twenty six asthmatic patients aged 21–59 years were selected for this randomised, double blind, parallel group study. The effect of 250 μg inhaled FP (MDI) administered twice daily was compared with that of placebo on BHR assessed using a dosimetric histamine challenge method. The dose of histamine inducing a decrease in forced expiratory volume in 1 second (FEV1 ) by 15% (PD15 FEV1 ) was measured before and 6, 12, 24 and 72 hours, and 2, 4 and 6 weeks after starting treatment, and 48 hours, 1 week and 2 weeks after cessation of treatment. Doubling doses of changes in PD15 FEV1 were calculated and area under the curve (AUC) statistics were used to summarise the information from individual response curves. Results: The increase in PD15 FEV1 from baseline was greater in the FP group than in the placebo group; the difference achieved significance within 72 hours and remained significant until the end of treatment. In the FP group PD15 FEV1 was 1.85–2.07 doubling doses above baseline between 72 hours and 6 weeks after starting treatment. BHR increased significantly within 2 weeks after cessation of FP treatment. Conclusions: A sustained reduction in BHR to histamine in patients with mild asthma was achieved within 3 days of starting treatment with FP at a daily dose of 500 μg. The effect tapered within 2 weeks of cessation of treatment.